The hydrogen paradigms: Technologies, country patterns of specialisation and dependence - Beatrice Negro; Giovanni Dosi; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
The adverse effects of the climate crisis call for a structural change in the economy toward less environmentally disruptive development pathways. To address decarbonisation, hydrogen seems to be the most promising element to complement renewable energy. However, the dominant technology for its production relies on hydrocarbons, while a radical transition would require the establishment of a green hydrogen technological paradigm. Green hydrogen production is also hampered by critical materials and geographic attributes that only some countries would meet. This may constitute a window of opportunity for latecomers' countries to pursue green industrialization or a condition for their exploitation. So, what are the drivers behind hydrogen technologies production? And, how do countries learn and consequently specialise? We tackle these questions investigating the technologies, products, and processes behind hydrogen production. Using trade data, we examine the pattern of countries' specialisation and dependence on raw materials. Our findings indicate that hydrogen technologies market is undergoing a transformation in their composition rather than expansion. Moreover, looking at the critical raw materials content of green hydrogen technology, we find a negative relationship between dependence on critical raw materials and the autonomous specialisation of countries in their related production.
Keywords: Q27; Q40; Q55; O1; 330; ecological transition; hydrogen paradigms; specialisation; dependency; mission-oriented policies